Physico-mechanical properties of kenaf pulp cellulose membrane cross-linked with glyoxal - Anis Syuhada Mohd Saidi,; Sarani Zakaria,; Chin, Hua Chia; Sharifah Nabihah Syed Jaafar,; Farah Nadia Mohammad Padzil, (Universiti Kebangsaan Malaysia, 2016)
Cellulose was extracted from kenaf core pulp (KCP) by a series of bleaching processes (D) and alkali treatment (E) in the sequence of (DEED) and pretreated with acid hydrolysis in room temperature for 6 hours. The pretreated and nontreated cellulose were dissolved in lithium hydroxide/urea (LiOH/urea) and subsequently used to produce cellulose membrane cross linked with various percentages of glyoxal from 2.5 to 20%. The effects of acid hydrolysis pretreatment on solubility, crystallinity and morphology were investigated. The acid hydrolysis pretreatment leads to higher solubility of the cellulose solution. The formation of cellulose II and crystallinity index of the cellulose membrane were examined by X-ray diffraction (XRD). Cellulose membrane without acid hydrolysis pretreatment cross linked with higher percentage of glyoxal has higher tensile strength compared with the treated cellulose.